Quality of life and thigh girth following anterior cruciate ligament reconstruction using hamstring autograft - Baig, Mirza A. (International Journal of Research in Orthopaedics, 2019)
Background: Arthroscopic anterior cruciate ligament reconstruction is commonly performed with intent to return earlier to normal activities, so graft selection becomes more important. The use of hamstring tendon autograft is supposed to have less postoperative morbidities. In this prospective study we assess the early post-operative complications. Methods: 25 patients were operated in Shadan Institute of Medical Sciences and Research Centre, Hyderabad, India, by the same surgeon and were assessed preoperatively, and 3 and 6 months after surgery. The hamstring and quadriceps strength were measured with PRIMUS RS machine. The patients were also assessed for their subjective complaints using International Knee Documentation Committee (IKDC) knee scoring system. Results: The peak power of flexion and extension of the knee joint significantly improved following the surgery which is essential for any athletic activities. Quadriceps and hamstring strengths were restored to 90%, which suggests that the grafting has been successful in restoring isometric strength. This is necessary to return to sporting activities. Power of hamstrings and quadriceps significantly improved following surgery. Quadriceps and hamstring endurance recovered and improved at the end of 6 months following surgery. Using IKDC scoring, nearly normal were 14, normal were 10 and abnormal 1. 3 patients (12%) presented with anterior knee pain. Sensory loss was noted in 6 patients (24%) at the end of 6 months following surgery. Swelling was noted in 5 patients (25%). Conclusions: Most morbidities are temporary in nature and do not significantly affect the patient’s activities.